PENYUSUNAN SKALA WELL-BEING ANAK (CWBS) - Mariska Aryono, Marcella (Widya Warta, 2018)
The majority of children’s well-being measurement is often rooted in Western culture in developed countries. Therefore, along with the increase of public awareness of children’s well-being in Surabaya, Indonesia, appropriate tools to measure it is greatly needed. The main objective of this study was to develop a valid and reliable instrument assessing the well-being levels of Indonesian children aged 11-15 years in Surabaya. The steps in scale development were carried out in four major phases. The first phase was the item generation and construction of the draft of the Children’s Well-being Scale (CWBS). Information from literature review and focus group discussions were used to generate the initial form (120 items) which were subjected to content validation by experts. In the second phase,a total of 294 participants completed the preliminary form of the instrument. Then, Cronbach’s Alpha(a=.91) and item-total correlation were done in the Preliminary form indicating that the instrument was internally consistent. In third phase, an additional 288 participants took the final form of CWBS. With this new sample, the CWBS were still internally consistent (a=.90). Confirmatory factor analysis was used to test the pre-hypothesized12 factor structure.Construct validity was assessed through analysis of correlations with three standardized tests: Mental Health Continuum-Short Form (r=.65), Personal Well-being Index-School Children (r=.61), and Revised Children Anxiety and Depression Scale-Short version (r=-.70).The CWBS were administered to a large group (N=708) for the norming of the test. Considering the result of the analysis of CWBSthat the 48 items had satisfying psychometric properties, it can be concluded that CWBS are valid and reliable instruments for Indonesian children.